LEADING LEARNING IN THE 21ST CENTURY: CHALLENGES AND STRATEGIES - Sitorus, Denny S. P.; Meilani, Yohana F. Cahya Palupi (Universitas Pelita Harapan, 2024)
This study aims to find out the challenges faced by educational leaders in learning in the 21st century and explore various effective strategies to overcome them. Rapid technological advances, diverse student populations, and evolving educational paradigms, educational leaders face various challenges in improving learning outcomes. The method used is through a comprehensive review of relevant literature and empirical studies. The results of the study indicate that various strategies are needed for effective leadership in the 21st century, including visionary leadership, collaborative approaches, innovative pedagogy, and continuous professional development. Successful leadership initiatives and have a positive impact on learning outcomes in the context of modern education. Ultimately, this article contributes to the ongoing discourse on educational leadership and provides insights and recommendations for educational leaders, policymakers, and practitioners to navigate the complexities of leading learning in the 21st century.